Qualitative Study on the Voices of Adolescents Living with Perinatally Acquired HIV in Selected Clinics in the Limpopo Province of South Africa - Rirhandzu Austice Mabasa; Livhuwani Muthelo; Linda Skaal; Tebogo Maria Mothiba (MDPI AG, 2023)
The disclosure of HIV status among adolescents living with perinatally acquired HIV (APHIV) has become one of the core challenges in the management of APHIV. Disclosure is a challenge that undermines positive advances and achievements in HIV management. There is limited literature on the voices of APHIV on disclosure of their status. This study aims to explore the current disclosure process and how it affects APHIV. A qualitative exploratory design was employed to conduct one-on-one in-depth interviews using a semi-structured interview guide. Purposive sampling was used to sample 21 APHIV in 16 selected health facilities in the Vhembe district of Limpopo Province, South Africa. Data were analyzed using Tesch's qualitative data method. The findings of this study reflect the gaps in the current disclosure process and guidelines while acknowledging the importance of disclosure to APHIV. A notable finding in this study is that most APHIV, especially those in early adolescence, did not want to know their HIV status due to the stigma attached to an HIV-positive diagnosis. This study suggests that proper training and support of parents and/or guardians in the disclosure process are needed, as they are the primary caregivers of APHIV. The disclosure of HIV status must be a comprehensive part of the management and care of HIV for APHIV. Furthermore, dedicated support programs should be developed and implemented to improve their lives post-disclosure.